The Wiggles. Halloween party [videorecording (DVD)] (Kino Lorber, 2021)
The Wiggles are having a Halloween Party and everyone is invited! Get ready for a spooktacular celebration. There's dress-ups aplenty, a Halloween feast, thirsty little vampires wanting cranberry juice, and, of course, lots of dancing including colorful skeletons doing the skeleton scat! Wiggle Town is decorated like never seen before with cobwebs, pumpkins, bats, and spiders. All the wiggly friends are there to join the party and sing and dance along to brand new songs.